Analisis Kelayakan Usaha Pengolahan Kedelai Menjadi Tahu di Desa Balai Nareh Kecamatan Pariaman Utara Kota Pariaman - Gusriati; Denis Setiawan; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2023)
The purpose of this study was to study the processing of soybeans into tofu at the Super Tofu Business and to analyze the business feasibility of the Super Tofu Business in Balai Nareh Village, North Pariaman District, Pariaman City. The basic method used in this research is descriptive method with the implementation of researching case studies. This research was conducted in Balai Nareh Village, North Pariaman District, Pariaman City on from February 13 to March 14 2021 with the respondents in this study being the owners and employees of the Tahu Super Business. Sources of data used are primary data and secondary data. Data analysis used quantitative descriptive analysis. Research results 1). Process of processing soybeans into tofu; (a) Washing and soaking soybeans, (b) Milling soybeans, (c) Boiling milled soybeans, (d) Filtering soybean juice, (e) Printing and cutting tofu, (f) Packing tofu in crates. 2). The Super Tofu business in Balai Nareh Village, North Pariaman District, Pariaman City is feasible to operate with an R/C of 1.49, a product BEP of 45.70 crates/day (548.4 kg) and a BEP of Rp. 60,502.52/crate (Rp. 5.041.87/kg). Revenue on total costs of Rp. 2,085,294.60. From the results of the research, it can be suggested: Tofu Super entrepreneurs should make a business license and expand the market in order to increase production capacity to get better income